ANALISIS HIGHER ORDER THINKING SKILLS (HOTS) PADA SOAL UJIAN AKHIR SISWA KELAS 6 KMI DALAM KELOMPOK MATA PELAJARAN DIROSAH ISLAMIYAH DI PONDOK MODERN TAZAKKA BATANG - Iqbal Faza Ahmad; Sukiman Sukiman (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2019)
This research aims to determine the composition of the final exam of Grade 6 students Kulliyatul Muallimin al-Islamiyah (KMI), a group of subjects of the honed Islamiyah in the modern cottage of Tazakka Batang from the level of thinking skills according to Bloom's taxonomy, and Know the characteristics of the Higher Order Thinking Skill (HOTS) contained in the final examination of the group's subjects. This research is qualitative descriptive-analytical research. Data collection is conducted using interviews and documentation. The validity of the data is tested using triangulation techniques, which include the triangulation of the source and method, and data analysis is done through transcript, coding, and verification. The results showed: 1) the composition of final examination of students in Grade 6 KMI Group of subjects (Tauhid, Fiqh, and Islamic date) judging by the level of thinking skills according to the dominant taxonomy of Bloom is the question that belongs to the Category level think remembering and understanding. (C1 and C2). There are a few questions that include thinking skills to apply, analyze, and evaluate (C3, C4, and C5), and there is no item that contains the ability to think creating (C6). 2) about the exam on the subjects of Tauhid, Fiqh, and Islamic date in the final exam of Grade 6 students in Pondok Modern Tazakka is based not on the special considerations about Higher Order Thinking Skill (HOTS). However, after the authors of the analysis, there are some questions about the group's subjects, which has some characteristic HOTS. The question of the most fulfilling the character of HOTS is about the test of Fiqh subjects, followed by Tauhid and History of Islam